OPTIMIZATION OF THE COST OF COMPOSITE MATERIAL (ROLLED CONCRETE) BY THE METHOD OF MATHEMATICAL MODELING OF THE EXPERIMENT - B.I. Saidmuratov; R. Safarov; B.B. Saidmuratov (European Journal of Life Safety and Stability (2660-9630), 2021)
The problem of optimizing the cost, composition and production technology of a composite material (roll concrete) by the method of experiment planning has been solved. A mathematical model has been built for the optimal determination of the cost of content. The prospects for using the model in future studies of composite materials are determined.